The importance of retail trade margins for calculating the carbon footprint of consumer expenditures: A sensitivity analysis - Milan Scasny; Radomir Mach; Jan Weinzettel (Charles University in Prague, Institute of Economic Studies (IES), 2020)
If environmental footprint attributable to various consumption patterns are evaluated, monetary transactions in the environmentally-extended input-output analysis need to be linked to household-specific expenditures. However, while the former are recorded in basic prices, the latter is typically recorded in purchaser's prices, adding a commodity tax and margins to basic prices. Product homogeneity assumption -inherent to input-output analysis - implies that two identical products sold to consumers with different retail trade margins are responsible for different footprints. In this paper we investigate how footprint attributable to Food and Goods is affected across household income classes if we relax the homogeneity assumption and assume different allocations of retail trade margins across the income classes. While different allocations affect footprints of the two Consumption groups significantly, in particular in the highest deciles, the effect on total footprint is very small, up to 10% even for two extreme cases of margins allocation.
Keywords: C67; R15; Q56; Q57; 330; Environmentally extended input-output analysis; carbon footprint; GHG emissions; retail trade margins; product homogeneity assumption; sensitivity analysis